ANALISIS PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN BESARNYA HARGA POKOK PRODUKSI (Studi Kasus pada CV Putra Jaya Rotan) - Djoko Kristianto, Jemy Hendra Widyanto, Rispantyo & (Universitas Slamet Riyadi, 2017)
This study uses the concept of a system of Activity Based Costing (ABC).Activity Based Costing System to make the activity as the central point of itsactivities. Information about the activity measured, recorded and provided in ashared database using Activity Based Costing system. It is based on the premise thatthe cause of the cost is the activities undertaken in a company, so naturally whenallocating indirect costs is based on the activity. Based on the above definition ofActivity Based Costing is a cost accounting system that will impose costs to productsor customers based on the resources consumed by identifying the cost of eachactivity required to produce a product or service. Researchers used Putra JayaRattan as an object in this study because of Putra Jaya Rotan because in thecalculation of factory overhead costs are still using traditional methods orconventional. In traditional or conventional whole system of indirect costs will becollected in a single grouping of cost (Cost Pool), then the total costs are allocatedto the basic allocation to a cost object. Base allocation used in Traditional System isin the form of hours, direct labor, direct labor costs, raw material costs, the numberof hours the engine, or the number of units produced. All this allocation basis is thecost driver is only related to volume or level of production that is used to allocateFactory Overhead. Results of determining the cost of production CV Putra JayaRattan using the traditional system of Rp1,500.000; per year for a total of Rp3.600.000.000;. While using the ABC method obtained a price of Rp 1.102.287,59per year with a total of Rp 2.645.490.216. The price difference using traditionalmethods and using the ABC method is Rp 397.712,41; whereas the difference in thetotal is Rp 954.509.784;.Keywords: implement activity based costing, cost of production.